Efek Angiogenesis Lumbrokinase terhadap Gambaran Histopatologi Jantung Tikus Galur Wistar Hipertensi Angiogenesis Effect of Lumbrokinase on the Cardiac Histopathology of Hypertensive Wistar Rat - Sharfina Sharfina; Suryono Suryono; Arief Suseno (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Hypertension remains a serious health problem it is dubbed as “the silent killer”. Pathophysiology of hypertension involve alteration of vascular structure. The use of anti hypertension leads to many side effects, and many people tend to choose natural therapy. The study aimed to investigate the effect of lumbrokinase on angiogenesis as a hypertension therapy agent. In true experimental design, 22 males wistar rat were divided into control group and treatment group (Lumbrokinase 0.5 gr/KgBW/day). The results showed that the systolic blood pressure decrease after therapy with lumbrokinase from 187 mmHg to 159 mmHg whereas diastolic blood pressure consistant at 80 mmHg after induction of hypertension as well as therapy of lumbrokinase. An examination of cardiac histopathology, there was an increasing number of blood vessels in the treatment group, 10.55± 1.44 compared to 7.45± 1.21 in control group. It can be concluded that lumbrokinase had an angiogenesis effect and decrease systolic blood pressure in hypertensive rat model. Keyword : Hypertension, lumbrokinase, vascular structure, angiogenesis.